Genetic Characteristics and Transcriptional Regulation of Sodium Channel Related Genes in Chinese Patients With Brugada Syndrome - Zhang, Ziguan; Chen, Hongwei; Chen, Wenbo; Zhang, Zhenghao; Li, Runjing; Xu, Jiajia; Yang, Cui; Chen, Minwei; Liu, Shixiao; Li, Yanling; Wang, TzungDau; Tu, Xin; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective: To investigate the genetic characteristics and transcriptional regulation of the SCN5A gene of Brugada syndrome (BrS) patients in China. Methods: Using PubMed, Medline, China National Knowledge Internet (CNKI), and Wanfang Database, Chinese patients with BrS who underwent SCN5A gene testing were studied. Results: A total of 27 suitable studies involving Chinese BrS patients who underwent the SCN5A gene test were included. A total of 55 SCN5A gene mutations/variations were reported in Chinese BrS patients, including 10 from southern China and 45 from northern China. Mutations/variations of BrS patients from southern China mostly occurred in the regions of the α-subunit of Nav1.5, including DIII (Domain III), DIV, DIII-DIV, C-terminus regions, and the 3'UTR region. Furthermore, we analyzed the post-transcriptional modifications (PTMs) throughout the Nav1.5 protein encoded by SCN5A and found that the PTM changes happened in 72.7% of BrS patients from southern China and 26.7% from northern China. Conclusions: SCN5A mutations/variations of BrS patients in southern China mostly occurred in the DIII-DIV to C-terminus region and the 3'-UTR region of the SCN5A gene, different from northern China. PTM changes were consistent with the mutation/variation distribution of SCN5A, which might be involved in the regulation of the pathogenesis of BrS patients.